ANATOMICAL STRUCTURE STUDY OF Solanum torvum Sw. - Agustina, Dwi; Ermayanti (BIOMA : Jurnal Ilmiah Biologi, 2025)
The Anatomy of Tekokak (Solanum torvum Sw.) is a plant that grows wild in the forest and its fruit is used as a vegetable. This study aims to complete the study of the anatomical structure of tekokak and identify typical microscopic characteristics that can be used as specific markers. This research is important in order to contribute to the scientific documentation of local plant taxonomy and support the utilization of plants in the fields of pharmacy, conservation, and as an a reference for botanical education in Biology. The research data were analyzed using a qualitative descriptive method by comparing the characteristics of the samples found with references. The results of this study include image data and qualitative descriptive data obtained from the anatomy of the roots, stems and leaves of Solanum torvum Sw The root of S. torvum Sw. consists of the epidermis, exodermis, a cortex layer made up of cortex parenchyma, endodermis with Casparian strips, a pericycle or pericambium layer, special medullary ray structures, and vascular tissues, xylem, and phloem. The stem part is composed of an epidermis with star-shaped non-glandular trichomes, lamellar collenchyma, cortex, endodermis layer, pericycle, vascular tissue comprising xylem and phloem, and pith. The anatomical difference between unbranched and branched stems lies in the arrangement of the vascular bundles, the thickness of the supportive tissue, and the complexity of the vascular tissue, indicating structural adaptations to the position and function of the stem. On the stem found scalariform trachea, annular trachea, reticulate trachea, thickened reticulate trachea, tracheid, fiber tracheid and libriform fiber. The leaf cross-section shows adaxial epidermis with cuboid-shaped cells and anisocytic stomata, palisade parenchyma, spongy parenchyma, abaxial epidermis with anomocytic stomata, and non-glandular star-shaped trichomes.